Direct Trade in the Specialty Coffee Market: Contributions, Limitations and New Lines of Research - Guimarães, Elisa Reis; dos Santos, Antônio Carlos; Leme, Paulo Henrique Montagnana Vicente; Azevedo, Angélica da Silva (Internext, 2020)
Study aim: we aimed to outline the direct trade of specialty coffees’ global research and adoption, highlighting its contributions, limitations and theoretical and empirical gaps, providing insights for future studies. Method: integrative systematic review of selected academic materials from the Web of Knowledge, SciELO, Scopus, Science Direct and Scholar Google databases, as well as technical materials from the Specialty Coffee Association and the Perfect Daily Grind portals, which were analyzed using the qualitative and open grid categorical content analysis technique. Main results: we identified three categories of contributions associated with Direct Trade - "Relationship and Coordination", "Origin and Sustainability" and "Quality and Differentiation" and three categories of its limitations - "Conceptual and Regulatory", "Execution and Monitoring" and "Potential of Transformation and Accessibility". Despite its potential to contribute to the promotion of the sustainability of this market, Direct Trade is not the only solution to the many and complex challenges of the activity. Therefore, it should be adapted to local realities and be carefully adopted, preferably in conjunction with other initiatives aimed at opening different markets and reaching different consumer audiences. Relevance/originality: this is the first systematic review of the subject, required by the rapid growth of studies in the field, despite its currentness and only recent expansion of the debate. Theoretical/methodological contributions: we presented a new concept of Direct Trade, subdivided the practice into two perspectives - relational and transactional – and elaborated a framework for its realization.